»... en Juvel – paa en Tribune«: Oplæseren, forfatteren og journalisten Herman Bang i 1904 - Lehrmann, Ulrik (Danske Studier, 2024)
1904 saw the publication of Herman Bang’s novel, Mikaël. At the same time he went on an extensive reading tour, travelled abroad to Prague and Vienna, and was a hard working journalist for the newspaper, København. The essay examines Bang’s various activities as reader of his own work, author and journalist in the year 1904 in order to shed light on the conditions under which he was a writer and a public person. In connection with his reading tour, light is shed on his activities as impresario and the traditional image of Bang as a reader of his own work is discussed. In connection with the publication of Mikaël it is shown how the public author and the private person part ways, even though the novel contained large personal investments on Bang’s behalf. Finally, Bang’s critical reflections on social and cultural matters are presented, reflections which in 1904 rose from his journalistic portraits of Danish provincial towns.